Pengaruh Latihan Menggunakan Alat Bantu terhadap Keterampilan Chest Pass Pada Peserta Ekstrakurikuler Bolabasket di SMP Negeri 1 Kota Sukabumi - Maulana, Irvan; Maulana, Firman; Nurina, Titis (FKIP Universitas Muhammadiyah Sukabumi, 2019)
Basket ball is a sport group consisting of two teams, 5 people for each team. The puprose of the game is to get as many points as possible by entering the ball into the opponent's ring. This study has a purpose, namely to find out the effect of training to use tools on chest pass skills. And to find out using net tools, car tires and targets for chest pass skills at 1 Junior High School.This research used quasi-experimental design used